2007
DOI: 10.1177/1363459307080862
|View full text |Cite
|
Sign up to set email alerts
|

Why modest geographic effects for asthma? Pharmaceutical treatment as neutralizing mechanism

Abstract: Research on geographic health effects has been greatly advanced with the development of multilevel statistical techniques but less is known about the possible mechanisms by which social and geographical environments may affect physical health. In spite of well-established relationships between asthma etiology and the broader living environments, multilevel research on asthma shows at best marginal geographic effects. Based on in-depth, open-ended interviews with 50 caretakers of school-age children (6-12 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This illustrates the findings of many studies that context-specific social, cultural, and economic circumstances shape perceptions of environment and health, and the relationship between the two (i.e., environmental health). This finding has been corroborated by more than a dozen studies that compared perceptions and responses of participants by differences in socioeconomic status, for example, by conducting focus groups and interviews with residents from the same city or neighborhood but from demographically distinct areas within the city or neighborhood (Bickerstaff and Walker 2001;Bolam et al 2006;Bush et al 2001;Day 2006Day , 2008Israel et al 2006;James and Eyles 1999;Kamphuis et al 2007;Popay et al 2003;Songsore and McGranahan 1998;Stevens et al 2004;Timmermans 2007;Wakefield et al 2001;Yen et al 2007). Additionally, day-to-day experience of environmental hazards, or health conditions, was reported to influence perception of environmental health.…”
Section: Factors That Influence Environmental Healthmentioning
confidence: 82%
See 3 more Smart Citations
“…This illustrates the findings of many studies that context-specific social, cultural, and economic circumstances shape perceptions of environment and health, and the relationship between the two (i.e., environmental health). This finding has been corroborated by more than a dozen studies that compared perceptions and responses of participants by differences in socioeconomic status, for example, by conducting focus groups and interviews with residents from the same city or neighborhood but from demographically distinct areas within the city or neighborhood (Bickerstaff and Walker 2001;Bolam et al 2006;Bush et al 2001;Day 2006Day , 2008Israel et al 2006;James and Eyles 1999;Kamphuis et al 2007;Popay et al 2003;Songsore and McGranahan 1998;Stevens et al 2004;Timmermans 2007;Wakefield et al 2001;Yen et al 2007). Additionally, day-to-day experience of environmental hazards, or health conditions, was reported to influence perception of environmental health.…”
Section: Factors That Influence Environmental Healthmentioning
confidence: 82%
“…Three of these were published in the journal EHP (Flocks et al 2001;Lipscomb et al 2005;McCauley et al 2001), and none were traditionally structured research articles. More than 30 articles described coding as a key component of analysis, with grounded theory being the most commonly cited analytic framework (Aragón et al 2001;Bush et al 2001;Green and Hart 1998;Hammal et al 2005;Larsson et al 2006;Schaefer-McDaniel 2007;Timmermans 2007;Trayers et al 2006). Proponents of grounded theory research have suggested that analysts approach the data with no substantive theories in mind.…”
Section: Theoretical Framework and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, neighboring households share the same exposure to heat and nearby traffic although actual lived experiences, exposure, and perceptions may differ substantially by time spent outdoors. Basically, behaviors at the individual or household level may substantially mitigate expected geographic effects of exposure (Timmermans 2007). As such, individual perceptions (as shaped by lived experience) may be key mediators that link objective conditions to some health outcomes (Poortinga et al 2008;Stafford and Marmot, 2003;Drukker and van Os 2003).…”
Section: Discussionmentioning
confidence: 99%